Proceso de ASC - OPERACION DE LA ESTACION RECEPTORA DE TIERRA EN EL CAMPUS DE EAFIT-LLANOGRANDE (2019)
Earth observation technologies are designated as those especially designed to obtain information on physical variables for monitoring purposes, ranging from simple pressure and temperature data to images and video of high resolution for geomorphology, security and defense applications. Between The most common earth observation devices and systems include: UAS (Unmanned Aereal Systems), which ranges from simple airplane models and multicopters, to sophisticated drones with military applications. The balloons stratospheric (High Balloning) and satellites (from those of large format to small satellites called picosatellites or CubeSats) also are part of these technologies and are systems that demand more complex land. The vast majority of Earth observation technologies are implemented on mobile devices, mainly aerial, and in some high-rise cases. In this sense, the problem addressed in the project consisted of maintain the mentioned earth observation systems in permanent communication with a ground station which is active and in good condition conditions, to ensure the information obtained against the risk of loss of the device due to an accident or some eventuality. Without a station terrestrial in operation and in good condition the mentioned devices Previously they would be nothing more than objects orbiting the earth.